2016
DOI: 10.7224/1537-2073.2015-028
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Deficits Questionnaire

Abstract: Background:Cognitive dysfunction affects approximately 43% to 70% of individuals with multiple sclerosis (MS) and is an important determinant of several functional outcomes in MS and quality of life. Brief neuropsychological test batteries have been developed specifically for use in MS and are widely used to aid clinicians in assessing levels of cognitive impairment in MS. Neuropsychologists and neurologists also frequently use briefer screening measures, such as the Perceived Deficits Questionnaire (PDQ), to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 35 publications
9
32
0
Order By: Relevance
“…6,7,8,22,23 The PDQ total score reported in this sample was similar to previously reported findings 6,8,22 and lower than the means in two studies, by approximately 5- 16 points. 7,23 The results of this analysis support the internal consistency reliability of the PDQ total scale.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…6,7,8,22,23 The PDQ total score reported in this sample was similar to previously reported findings 6,8,22 and lower than the means in two studies, by approximately 5- 16 points. 7,23 The results of this analysis support the internal consistency reliability of the PDQ total scale.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that as perceived deficits increase so do feelings of depression, is consistent with other studies, 4,6,7,8 suggesting that self-reported cognitive difficulties are related to depressive symptoms. Importantly, these are correlations that demonstrate associations not causality.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations